2022
DOI: 10.1111/php.13756
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Robust and Reliable Response from a Potent Osmium‐Based Photosensitizer Via Lipid Nanoformulation

Abstract: Osmium (Os) based photosensitizers (PSs) are a unique class of nontetrapyrrolic metal-containing PSs that absorb red light. We recently reported a highly potent Os(II) PS, rac-[Os (phen) 2 (IP-4T)](Cl) 2 , referred to as ML18J03 herein, with light EC 50 values as low as 20 pM. ML18J03 also exhibits low dark toxicity and submicromolar light EC 50 values in hypoxia in some cell lines. However, owing to its longer oligothiophene chain, ML18J03 is not completely water soluble and forms 1-2 μm sized aggregates in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…We previously showed that DSPE-mPEG 2000 micelles are an efficient and robust platform that stably encapsulate a hydrophobic conjugate of the PS benzoporphyrin derivative and cholesterol, even when liposomes fail to do so [18]. Our recent study has shown that ML18J03, when formulated in 10.2 nm DSPE-mPEG 2000 micelles, exhibits low dark toxicity, submicromolar EC 50 values in hypoxia, retains its photoactivity in normoxia, and provides a significant reduction in inter-assay variability of ML18J03 [10]. Of particular significance to this study, the formulation of ML18J03 into DSPE-mPEG 2000 micelles increases its luminescence quantum yield in PBS from 9.8 × 10 −5 to 1.3 × 10 −3 , Figure 1 [10].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…We previously showed that DSPE-mPEG 2000 micelles are an efficient and robust platform that stably encapsulate a hydrophobic conjugate of the PS benzoporphyrin derivative and cholesterol, even when liposomes fail to do so [18]. Our recent study has shown that ML18J03, when formulated in 10.2 nm DSPE-mPEG 2000 micelles, exhibits low dark toxicity, submicromolar EC 50 values in hypoxia, retains its photoactivity in normoxia, and provides a significant reduction in inter-assay variability of ML18J03 [10]. Of particular significance to this study, the formulation of ML18J03 into DSPE-mPEG 2000 micelles increases its luminescence quantum yield in PBS from 9.8 × 10 −5 to 1.3 × 10 −3 , Figure 1 [10].…”
Section: Introductionmentioning
confidence: 89%
“…ML18J03 was synthesized as previously described [8]. Aqueous Mic-ML18J03 preparations were obtained by formulating the PS in DSPE-mPEG 2000 micelles according to our previously published protocol [10]. Briefly, 0.085 µmol of ML18J03 (1 mg/mL stock in methanol) was mixed with 0.71 µmol DSPE-mPEG 2000 (25 mg/mL stock in chloroform; NOF America Coorporation, White Plains, NY, USA) to provide 11 mol% PS with respect to total lipid content.…”
Section: Preparation Of Free Ml18j03 and Mic-ml18j03mentioning
confidence: 99%
See 2 more Smart Citations
“…Both TLD-1433 and TLD-1633 have significant batch-to-batch variability in cellular phototoxicity studies (1). The current highlighted paper by McFarland et al (2) addresses this last point by finding a means of improving run-torun consistency for highly potent and lipophilic drugs that are prone to aggregation. This work demonstrates the utility of their methods with highly potent Os photosensitizers (PSs), but the work is relevant to other metallodrugs (3) and is also relevant to lipophilic organic photosensitizer drugs as well.…”
Section: Commentarymentioning
confidence: 99%